1989
DOI: 10.1002/anr.1780320506
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the collagen‐like region of C1q in sera of patients with autoimmune rheumatic diseases

Abstract: Antibodies to the collagen‐like region of C1q have recently been observed in sera of patients with systemic lupus erythematosus (SLE). In this study, we documented that these antibodies were present in 47.3% of SLE patient sera, whereas they were uncommon in sera from patients with rheumatoid arthritis (2.8%) and Sjögren's syndrome (12.8%), as well as in normal sera (6.4%). Markedly elevated antibody levels (>4 SD above the normal mean) were observed almost exclusively in sera of patients with SLE. Levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 28 publications
4
53
0
1
Order By: Relevance
“…For comparison, in unselected series of patients with SLE, the prevalence of IgG antibodies to Clq-CLR has varied from 17% to 46% (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, in unselected series of patients with SLE, the prevalence of IgG antibodies to Clq-CLR has varied from 17% to 46% (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antibodies to Clq-CLR was detected with an enzyme-linked immunosorbent assay (ELISA) system, as previously described (13). Briefly, Clq was isolated from outdated plasma and Clq-CLR was prepared with previously described methods (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of fluid phase Clq only partially inhibited the binding of anti-C1 qAb to solid phase Clq. This can be explained by the fact that anti-ClqAb in patients' sera only react with either soHd phase or immune complex (ICs) bound Clq [18]. The fluid phase Clq preparation used can partially inhibit anti-ClqAb activity because of the presence of aggregates of Clq.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of IgG class autoantibodies to C1q in lupus was first reported in 1984 [146]. Further investigations revealed that the majority of IgG binding to C1q in solid phase assays was attributable to autoantibodies reacting with an epitope only exposed in structurally modified C1q [147]. Such a change in structure, to reveal a 'neo-epitope', may follow proteolytic cleavage, a conformational change following activation or following binding to another protein.…”
Section: Development and Pathogenicity Of Antibodies Against Acute-phmentioning
confidence: 98%